Analisis Penggunaan Media Pembelajaran untuk Meningkatkan Pemahaman Sistem Saraf pada Siswa - Zega, Hajriah Nur Rahmat; Gowasa, Desdayanti; Lase, Natalia Kristiani (Indo-MathEdu Intellectuals Journal, 2024)
The human nervous system is a learning material that includes a lot of abstract material that cannot be directly observed by students. With Augmented Reality (AR) technology, students can learn in person anytime and anywhere. The purpose of this study is to analyze the use of digital learning media in nervous system learning materials and find the right type of learning media to improve student learning outcomes and understanding of the material. This study uses a qualitative approach with a literature study method. The data sources obtained from this study are primary data and secondary data, according to Sugiyono, the primary data comes from the literature journals that have been collected, and the secondary data comes from relevant book and website references. The first step is to collect data from various sources. For the purpose of this study, the data sources used came from 13 recent journals selected based on certain criteria, which had articles relevant to the research topic. Once the journal is collected, a journal summary is created that includes the name, type, title, year of publication, location, objectives, methods, and research results. The results of the descriptive analysis of national journals show that increasing students' interest and learning outcomes is influenced by learning nervous system material with digital media. Augmented Reality (AR) is the most effective learning medium to increase students' interest and learning outcomes